100 Years Anniversary of the Bohr Model of the Atom: How Chemistry Freshmen Understand Atomic Structure of Matter - Hadžibegović, Zalkida; Galijašević, Semira (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2013)
Hundred years ago the Danish physicist Niels Bohr presented his model of the atom for what he received Nobel Prize. His theory led to the revolutionary development of science in the beginning of 20th century. Later one, quantum mechanics developed a new theory explaining all the shortcomings of Bohr's model. However Bohr's atom theory is presented and studied in most introductory General Chemistry textbooks. This anniversary was an opportunity to see how science students understand and visualize the structure of the atom. The data reported in this paper derived from a pilot research with 58 chemistry freshmen, were collected to explore their ideas of an atom, their knowledge about the Bohr model of the atom, and history and philosophy of science approach to Bohr atomic theory. Students' knowledge about Bohr's postulates is in agreement with chemistry textbook content except the part about Bohr's idea of angular momentum quantization, which they discuss within the General Physics 2 course. Using historical point of view when studying Bohr's theory and his model of the hydrogen atom can help students to understand contemporary theory of the atom better.